Aesthetic value of Rumah Kuttai - Awang, Arita Hanim; Mohd. Din, Shamzani Affendy; Jahn Kassim, Puteri Shireen; Ab Jalil, Nurlelawati; Abdul Rahman, Julaila (2019)
The introduction of Rumah Kutai as one of living heritage lab under Kulliyyah Of Architecture & Environmental Design has been a great contribution to the community of International Islamic University Of Malaysia especially for the lecturers and students to appreciate more on Malay traditional house. Rumah Kutai or known to be the traditional malay house of perak, one of the state at the North West of Malaysia. Rumah Kutai has a signature house looks simple, steep with dominantpitched roof shading the main house. Besides, the roof also has a minor extension to mark the entrance to the house. It has also gable ends that have a weaved bamboo panel to allow for air movement which act as natural ventilation with in the space inside the roof.